Intermittent Hypoxia and Prolonged Suboxia Measured In situ in a Marine Sponge - Lavy, Adi; Keren, Ray; Yahel, Gitai; Ilan, Micha (Frontiers in Marine Science, 2016)
High Microbial Abundance (HMA) sponges constitute a guild of suspension-feeding sponges that host vast populations of symbiotic microbes. These symbionts mediate a complex series of biogeochemical transformations that fuel the holobiont’s metabolism. Although sponges are aerobic animals, suboxic and anaerobic bacteria are known to reside within their bodies. However, little is known about the chemical characteristics of the sponge environment in which they occur and almost no data are available regarding the dissolved oxygen (DO) dynamics inside the holobiont in its natural habitat. In this study we examined the oxygen dynamics in situ in the HMA sponge Theonella swinhoei. A submersed data-logging system equipped with micro-sensors was used to continuously record DO concentrations inside the sponge body and in its outflowing water for up to 48 hours. Actively pumping sponges exhibited high DO removal rates punctuated with short bursts of extreme DO uptake (>90 µmol DO Lpumped-1), never before observed in sponges. Such a high DO removal rate indicates the consumption of a considerable amount of reduced matter, far exceeding the available sources in the surrounding water of the oligotrophic coral-reef ecosystem inhabited by this sponge. The inner body of the sponge remained suboxic throughout the experiments, with short events of further rapid DO concentration decline. Moreover, DO concentrations measured in the body and in the outflowing water were found to be uncorrelated. Our findings support a previous hypothesis of bacterial symbiont farming by the sponge as a potential source for acquiring reduced material. Moreover, this suggests a complex and highly localized control of the holobiont’s metabolism, probably associated with the microbial community’s metabolism. Our results indicate that temporal micro-environments exist in the sponge at alternating locations, providing suitable conditions for the activity of its anaerobic microbial symbionts.